Innovative Learning Approaches in Sports: Comparing Teaching at the Right Level and Classical Methods for Drive Stroke Mastery - Liskustyawati , Hanik; Sabarini, Sri Santoso; Syaifullah, Rony; Waluyo; Mukholid, Agus; Putro, Baskoro Nugroho; Suratmin (Universitas Pendidikan Ganesha, 2024)
The lack of teaching approaches tailored to students' skill levels often hinders the development of sports abilities, including drive stroke proficiency in tennis. This study aims to analyze the differences in the effectiveness of the Teaching at the Right Level (TaRL) approach compared to classical methods in improving drive stroke skills. The research utilized an experimental method with a 2 x 2 factorial design. The sample consisted of 64 randomly selected students, and data collection employed the Forehand Groundstroke Tennis Test Accuracy by Jennifer Love Hewitt. Data analysis was performed using SPSS version 25.0, including prerequisite tests for normality and homogeneity (α = 0.05) and factorial analysis. The results revealed that the TaRL approach significantly influenced drive stroke skills compared to the classical approach (Sig = 0.00 < 0.05). However, no significant differences were found based on arm muscle power and gender (Sig = 0.667 > 0.05), nor were there interactions among teaching approach, arm muscle power, and gender on drive stroke skills (Sig = 0.490 > 0.05). This study concludes that the TaRL approach is more effective than the classical method in improving drive stroke skills. These findings underscore the importance of implementing teaching methods tailored to students' abilities to optimize sports learning outcomes.